The impact of subsidies on projected heat pump adoption and residential heating emissions in Massachusetts - Emma K Walter; Matthew J Eckelman (Environmental Research: Infrastructure and Sustainability)
Space heating is a significant contributor to residential building emissions, and many policies have leveraged subsidies for heat pumps as a step toward building electrification and broader decarbonization goals. Massachusetts (MA) aims to reduce residential heating emissions to 0.8 MtCO _2 eq per year by 2050, offering a $10 000 subsidy for whole home heat pumps. This study examines the impact of various state-level subsidy scenarios on adoption rates, emission reductions, and associated co-benefits in MA and the region. Using Global Land-use, Impact, and Policy Simulator Environment, a graphical interface for the integrated assessment model global change assessment model-USA, this study explores state-level scenarios including current and full subsidy rates, as well as forced adoption, to predict future emissions and heat pump use. Results show that under the current subsidy rates, 2050 residential heating emissions in MA would triple the state’s target. Even under the most aggressive scenario, heat pump adoption reached only 88% by 2050, with emission still 62% above the target. The emission impact and electricity demand on neighboring states was small, owing to programs like the Regional Greenhouse Gas Initiative and Renewable Portfolio Standard programs that limit emissions in the region. A public benefit-cost analysis found the highest cost-effectiveness ratio, 12.5, under a 100% subsidy scenario, with current subsidy rates returning a cost-effectiveness ratio of 6.7. These findings suggest that financial subsidies alone may not be sufficient and additional decarbonization strategies are needed to meet emission targets.